2016
DOI: 10.1016/j.applthermaleng.2016.05.155
|View full text |Cite
|
Sign up to set email alerts
|

Comparative research on air conditioner with gas-injected rotary compressor through injection port on blade

Abstract: Economizer technology has become a critical method to improve the performance of air conditioners with rotary compressor in low ambient temperature. A novel vapor injection structure on the blade of the rotary compressor has been proposed in previous research to overcome the drawback of the traditional cylinder injection structure. Based on a verified numerical system model, the performance of an air conditioner adopting different economized rotary compressors has been investigated. The results indicate that: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Silindir enjeksiyonlu klimayla karşılaştırıldığında, palet enjeksiyon yapısının, klimanın ısıtma kapasitesini % 12,5-15,7 ve COP'yi % 1,5-4,1 arttıracağını belirlemişlerdir. Ancak, palet enjeksiyonlu döngüsel kompresörün sistem ısıtma kapasitesinin, tüm çalışma koşullarında iki gövdeli döngüsel kompresörünkinden %4,7 daha az olduğu görülmüştür [106]. Ayrıca, kompresördeki eksantrikliğin doğru ölçüde değiştirilmesi ile enjeksiyon alanında %40-%70 aralığında artış sağlanabileceğini gözlemlemişlerdir [102].…”
Section: şEkil 8 Buhar Enjeksiyon Türleri (Steam Injection Types) [99]unclassified
“…Silindir enjeksiyonlu klimayla karşılaştırıldığında, palet enjeksiyon yapısının, klimanın ısıtma kapasitesini % 12,5-15,7 ve COP'yi % 1,5-4,1 arttıracağını belirlemişlerdir. Ancak, palet enjeksiyonlu döngüsel kompresörün sistem ısıtma kapasitesinin, tüm çalışma koşullarında iki gövdeli döngüsel kompresörünkinden %4,7 daha az olduğu görülmüştür [106]. Ayrıca, kompresördeki eksantrikliğin doğru ölçüde değiştirilmesi ile enjeksiyon alanında %40-%70 aralığında artış sağlanabileceğini gözlemlemişlerdir [102].…”
Section: şEkil 8 Buhar Enjeksiyon Türleri (Steam Injection Types) [99]unclassified
“…Ma et al [11] evaluated the thermodynamic performance of these two quasi-two-stage compression cycles (FT type and subcooler type), and reported that, in comparison to single-stage compression cycles, the FT structure presented the following advantages: the heating capacity and the COP were higher by a factor of 8.6% and 6%, respectively, at the evaporation temperature of À15 C and the condensation temperature of 45 C. Wang et al [12] classified quasi-two-stage compression systems among the economizer technologies. Gas supplementation using a rotary compressor under low-temperature environment is reported to increase the system COP by 1.5-4.1%.…”
Section: Structural Characteristics Of Frs-hthps and Rrs-hthps 21 Analysis Of The Characteristics Of The Quasi-two-stage Compression Cyclmentioning
confidence: 99%